The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.jcmg.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Cardiovascular Magnetic Resonance in Acute Myocarditis

Abstract: Novel CMR mapping techniques provide high diagnostic accuracies for the diagnosis of acute myocarditis and constitute promising successors of the classic elements of the LLC for routine diagnostic protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(110 citation statements)
references
References 31 publications
6
92
1
5
Order By: Relevance
“…Additionally, we do not distinguish patients with dilated cardiomyopathy, although myocarditis is a known underlying cause of dilated cardiomyopathy. Even using modern diagnostic techniques, accurate diagnosis of myocarditis is limited [35]. It is important to note that our study did not investigate the diagnostic accuracy of these techniques, rather compared the association of ECG and CMR findings in a real-world setting of patients with a clinical referral of suspected myocarditis.…”
Section: Limitationsmentioning
confidence: 99%
“…Additionally, we do not distinguish patients with dilated cardiomyopathy, although myocarditis is a known underlying cause of dilated cardiomyopathy. Even using modern diagnostic techniques, accurate diagnosis of myocarditis is limited [35]. It is important to note that our study did not investigate the diagnostic accuracy of these techniques, rather compared the association of ECG and CMR findings in a real-world setting of patients with a clinical referral of suspected myocarditis.…”
Section: Limitationsmentioning
confidence: 99%
“…The metaanalysis shows that LLC have been firmly established in clinical practice and that the use of native of T1 mapping can further enhance CMR accuracy in diagnosing myocarditis. These findings are supported by another meta-analysis including 22 studies by Kotanidis et al (50), which similarly concludes that native T1 mapping has a significantly higher diagnostic accuracy compared to all other index tests: native T1 mapping showed an area under the curve (AUC) of 0.95 compared to T2 mapping with an AUC of 0.88 and LLC of 0.81 and will therefore likely be implemented in the upcoming updated Lake Louise Criteria. Additionally, the authors showed that T2 mapping was superior to T2-weighted and EGE imaging, suggesting that both EGE and T2-weighted imaging could be replaced by T1 -and T2 mapping respectively (50).…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 59%
“…In particular, T1 and T2-weighted images evaluate hyperemia and capillary leakage, necrosis and fibrosis, and intracellular and interstitial edema -3 markers of tissue injury [5]. A recent systematic review and meta-analysis showed that native T1 image can improve diagnostic accuracy of cardiac magnetic resonance in acute myocarditis [6]. Endomyocardial biopsy (EMB) confirms the diagnosis of myocarditis and recognizes the etiology and the type of inflammation.…”
Section: Discussionmentioning
confidence: 99%